Top Incomes in Ireland: Reconciling Evidence from Tax Records and Household Survey Data - Callan, T.; Doorley, K.; McTague, A. (Statistical Society and Social Inquiry of Ireland, 2021)
There are substantial divergences between the pictures of income inequality provided by household survey data for the full population and analyses based on administrative data generated by the income tax system focusing on the share of income accruing to the top of the income distribution. Our analysis, similar to international work on this topic, finds that differences in concepts and measures play a very substantial role in explaining these differences in the Irish context. When analyses of household data and administrative data are aligned using the same concepts and measures, the contrasts are much reduced. Average incomes for the top 1% of the population do appear to be higher in tax return data than in SILC, again in line with international findings. There is a strong case for examining potential adjustments to survey data to ensure better representation of income levels at the very top of the income distribution. Such adjustments combine information from tax returns and household surveys to give better representation of top incomes, while retaining the advantages of household data’s perspectives on low incomes and household context
read before the Society, 22nd October 2020
Keywords: inequality; income distribution; 314.15